Pretreatment lymphocyte‐to‐monocyte ratio as an independent prognostic factor for head and neck cancer. Issue 2 (12th September 2016) - Kano, Satoshi; Homma, Akihiro; Hatakeyama, Hiromitsu; Mizumachi, Takatsugu; Sakashita, Tomohiro; Kakizaki, Tomohiko; Fukuda, Satoshi
Abstract: Background: The purpose of this study was to analyze the relationship between pretreatment inflammatory markers and the prognosis of patients with oropharyngeal, hypopharyngeal, and laryngeal cancers. Methods: The data for 285 patients treated with curative intent by concurrent chemoradiotherapy (CRT) were obtained and their pretreatment inflammatory markers, including neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and lymphocyte‐to‐monocyte ratio (LMR) were calculated. Results: Significant relationships were observed between a high NLR and oropharyngeal or hypopharyngeal cancer, T3 to T4, N2b to N3, and clinical stage III to IV, whereas significant relationships were observed between a high LMR and laryngeal cancer, T1 to T2, and clinical stage I to II. With regard to survival outcomes, a high NLR, a high PLR, and a low LMR were all significantly associated with decreases in overall survival (OS) and disease‐free survival (DFS). Furthermore, multivariate analysis showed that LMR was an independent prognostic factor. Conclusion: Pretreatment LMR was found to be an independent prognostic factor for patients with head and neck cancers treated by concurrent CRT. © 2016 Wiley Periodicals, Inc. Head Neck 39: 247–253, 2017